Investors in Private Equity Funds Theory, Preferences and Performances - Hobohm, Daniel; SpringerLink (Online service) (Wiesbaden : Gabler Verlag : Imprint: Gabler Verlag, 2010)
Daniel Hobohm analyses more than 17 000 investments by more than 1800 international investors in more than 2400 private equity and venture capital funds over the last two decades. He compares different investor types in their fund preferences, home bias and investor responses to market shocks. Further, he determines returns by investor type and the effect of external advisors on fund investment returns. The author analyses the role of risk-taking when choosing VC funds and, in a unique investigation, the role of the proximity of the investor to the fund. His analysis sheds light on the intransparent private equity market and highlights the significance of the close investor-fund interaction for investment success.
Theory of Fund Investments -- Limited Partners -- Data -- LP Investment Preferences -- LP Investment Performance -- Conclusion.
Keywords: Public finance; Finance; Public Economics; Finance, general